"Walking the talk": the role of frontline supervisors in preventing workplace accidents. Issue 3 (3rd May 2020) - Kessler, Stacey R.; Lucianetti, Lorenzo; Pindek, Shani; Spector, Paul E.
ABSTRACT: Most existing safety research focuses on climate and leadership, with most leadership studies investigating transformational leadership, which is likely to be more impactful when exhibited by executives that by frontline supervisors. Therefore, focusing on frontline supervisors, we investigate how leaders who "walk the talk", by directly modelling safety behaviours, might encourage subordinates to behave more safely. Using a three-level sample consisting of 579 employees and their supervisors working in 161 groups within 53 organizations, we test a multisource multilevel indirect effects model. Results indicate that safety climate and supervisors modelling safety compliance explain unique variance in safety outcomes. We then addressed an unanswered question concerning whether safety climate is best conceptualized as a group or organizational-level phenomenon, finding that the group-level assessment of safety climate explained more variance in safety outcomes than the organizational-level assessment of safety climate. Both sets of results are consistent with social information processing theory and social learning theory, which highlight the immediate social environment's influence on employees' behaviour.